2016
DOI: 10.1002/ajmg.a.37655
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory system involvement in Costello syndrome

Abstract: Costello syndrome (CS) is a multisystem disorder caused by heterozygous germline mutations in the HRAS proto-oncogene. Respiratory system complications have been reported in individuals with CS, but a comprehensive description of the full spectrum and incidence of respiratory symptoms in these patients is not available. Here we report the clinical course of four CS patients with respiratory complications as a major cause of morbidity. Review of the literature identified 56 CS patients with descriptions of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Complex pulmonary and airway co‐morbidities are present in a significant proportion of neonates and infants with CS (Gomez‐Ospina et al, ; Myers et al, ), and are more common and severe than in the general population, even accounting for prematurity. Upper and lower airway abnormalities as well as abnormalities of the lung parenchyma such as chronic lung disease occur.…”
Section: Respiratory and Otolaryngologic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex pulmonary and airway co‐morbidities are present in a significant proportion of neonates and infants with CS (Gomez‐Ospina et al, ; Myers et al, ), and are more common and severe than in the general population, even accounting for prematurity. Upper and lower airway abnormalities as well as abnormalities of the lung parenchyma such as chronic lung disease occur.…”
Section: Respiratory and Otolaryngologic Findingsmentioning
confidence: 99%
“…Nasal papillomata are common in older individuals and may require removal. Obstructive or central sleep apnea (Della Marca et al, ), ongoing parenchymal lung injury, or the evolution of cardiopulmonary disease require early recognition and treatment (Gomez‐Ospina et al, ).…”
Section: Respiratory and Otolaryngologic Findingsmentioning
confidence: 99%
“…These ultrasound features, either in isolation or combination, are considered an indication for follow‐up genetic testing 18,19 . The ability to identify pregnancies at risk for a RASopathy can help provide anticipatory guidance for associated adverse perinatal complications including respiratory complications, cardiac problems, and lymphatic abnormalities which can be difficult to detect solely by second trimester ultrasound or fetal echocardiogram 12,20 . For instance, Myers et al 12 reported congenital heart defects in 68% of newborns with Noonan syndrome, but a prenatal detection rate of only 21%.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory and otolaryngologic findings as well as cardiovascular abnormalities have also been described in patients with CS (Table 1) [1]. Notably, airway problems requiring tracheostomy has been reported as rare complication in patients with CS and different HRAS variants; [1,14,17] thus, this finding is not related to specific (rare common) variants. On the other hand, individuals showed milder facial features than patients with HRAS p.Gly12Ser; this is more in keeping with findings seen in individuals with rare HRAS variants affecting residues Thr 58 , Gly 60 , Lys 117 or Ala 146 (Table 1) [1-3, 5, 7, 9-11, 18].…”
Section: Discussionmentioning
confidence: 96%